MP02: Diagnostic, medical, and surgical interventions that reduce emergency hospital admissions: a systematic review of systematic reviews of 215 randomized controlled trials. (May 2019) - Collins, D.; Bobrovitz, N.; Fletcher, B.; Onakpoya, I.; Heneghan, C.; Mahtani, K.
Abstract : Introduction : Emergency hospital admissions are a growing concern for patients and health systems, globally. The objective of this study was to systematically review the evidence for diagnostic, medical, and surgical interventions that reduce emergency hospital admissions.Methods : We conducted a systematic review of systematic reviews by searching MEDLINE, PubMED, the Cochrane Database of Systematic Reviews, Google Scholar, and grey literature. Systematic reviews of any diagnostic, surgical, or medical interventions examining the effect on emergency hospital admissions among adults were included. The quality of reviews was assessed using AMSTAR and the quality of evidence was assessed using GRADE. The subsequent analysis was restricted to interventions with moderate or high-quality evidence only.Results : 13 051 titles and abstracts and 1 791 full-text articles were screened from which 42 systematic reviews were included. The reviews included an underlying evidence base of 215 randomized controlled trials with 135 282 patients. Of 20 unique diagnostic, medical, and surgical interventions identified, four had moderate (n = 4) or high (n = 0) quality evidence for significant reductions in hospital admissions in five patient populations. These were: cardiac resynchronization therapy for heart failure and atrial fibrillation, percutaneous aspiration for pneumothorax, early/routine coronary angiography for acute coronary syndrome (alone or comorbid with chronic kidney disease), and natriuretic peptide guided therapy for heart failure.Conclusion : We identified four interventions across five populations that when optimized, may lead to reductions in emergency hospital admissions. These finding can therefore help guide the development of quality indicators, standards, or practice guidelines.